Information technology for constructing the composite indices for data of different types used in medical and environmental studies - Antomonov, M.Yu. (Кибернетика и вычислительная техника, 2018)
The purpose of the paper is to develop a generalized information technology for constructing composite indices for different types of data used in medical and environmental studies. Метою статті є розроблення узагальненої інформаційної технології конструювання комплексних показників для різних типів даних, які використовуються в медико-екологічних дослідженнях. Целью статьи является разработка обобщенной информационной технологии конструирования комплексных показателей для различных типов данных, используемых в медико-экологических исследованиях.